Solvent-induced transformations in ferromagnetically coupled (Ni4L4) clusters - Cindrić, Marina (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
Research examines magnetic systems based on polynuclear complexes, focusing on cubane-like Ni(II) clusters. The study demonstrates how solvent exchange between methanol and water triggers reversible structural changes affecting magnetic properties. Various cluster configurations were isolated and characterized using multiple analytical techniques including crystallography, thermal analysis, and magnetometry.